Control of a direct matrix converter with modulated model predictive control - Vijayagopal, Manjusha; Zanchetta, Pericle; Empringham, Lee; De Lillo, Liliana; Tarisciotti, Luca; Wheeler, Patrick (Institute of Electrical and Electronics Engineers, 2017)
This paper investigates the use of a model- predic-tive control strategy to control a direct matrix converter. The proposed control method combines the features of the classical Model Predictive Control and the Space Vector Modulation technique into a Modulated Model Predictive Control. This new solution maintains all the characteristics of Model Predictive Control (such as fast transient response ,multi-objective control using only one feedback loop, easy inclusion of non-linearities and constraints of the system, the flexibility to include other system requirements in the controller) adding the advantages of working at fixed switching frequency and improving the quality of the controlled waveforms. Simulation and experimental results employing the control method to a direct matrix converter are presented.